2019
DOI: 10.1002/cam4.1931
|View full text |Cite
|
Sign up to set email alerts
|

Very long‐term survivors among patients with metastatic soft tissue sarcoma

Abstract: Background Metastatic soft tissue sarcomas (STS) are a group of rare and heterogeneous mesenchymal tumors with a poor prognosis. The aim of this study was to evaluate the incidence of long‐term survivors and describe their presentation and management in a large cohort of patients with metastatic STS. Methods We collected information of patients with metastatic STS managed in Centre Leon Berard between 1985 and 2015 aiming to compare the group of patients alive 5 years after the diagnosis of metastases vs the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…147,148 Chemotherapy is the standard form of treatment for metastatic sarcomas; however, the reported median overall survival is only 12 months and <10% of patients have a 5year overall survival rate. 15,149,150 There is therefore clearly a need for more effective therapies as the traditional approaches have been mostly ineffective. Targeted therapies may overcome the current therapeutic limitations; however, most sarcoma subtypes have alterations in many signaling pathways and therefore effective therapy will probably need to target a range of pathways.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…147,148 Chemotherapy is the standard form of treatment for metastatic sarcomas; however, the reported median overall survival is only 12 months and <10% of patients have a 5year overall survival rate. 15,149,150 There is therefore clearly a need for more effective therapies as the traditional approaches have been mostly ineffective. Targeted therapies may overcome the current therapeutic limitations; however, most sarcoma subtypes have alterations in many signaling pathways and therefore effective therapy will probably need to target a range of pathways.…”
Section: Molecular Targeted Therapymentioning
confidence: 99%
“…13 Furthermore, the 5-year survival rate for localized STS is about 50% and <10% for metastatic STS. 14,15 While a proposed molecular targeted approach to treatment has gained traction, the molecular mechanisms that drive the sarcoma cells of origin to a transformed phenotype remain to be elucidated. This review, therefore, focuses on the key molecular mechanisms identified to be associated with sarcomagenesis and their potential as novel targets for sarcoma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The aim was to estimate the survival time of the patients until death from sarcoma as a function of covariates such as the age at diagnosis, sex, tumor site, cancer spread (metastasis), and the margin status. The variables selected for estimating the survival probabilities were previously reported to be related to long‐term sarcoma survival (Carbonnaux et al., 2019; Daigeler et al., 2014, among others).…”
Section: Application To Real Datamentioning
confidence: 99%
“…Dos portadores de metástases, < 20% estarão vivos em dois anos. 15 Além da presença de metástases, as margens cirúrgicas desses sarcomas possuem grande impacto no prognóstico. 16,17 Apesar de menos frequentes no grupo pediátrico, os SPM podem acometer esta faixa etária, e o rabdomiossarcoma é o SPM mais comum.…”
Section: Aspectos Clínicosunclassified